The Effect of Industrialization and Population Growth on Migration - Mustapita, Arini Fitria; Khalikussabir, Khalikussabir (University of Merdeka Malang, 2019)
Industry is an important thing in development. It is based on the reasons, industrialization can increase income and prosperity quickly. Industrialization is also a factor that encourages people to migrate. The population prefers to migrate on urban areas which have a greater employment opportunities in the industrial sector. This study aims to determine the effect of industrialization and population growth on internal migration in Malang City. The analytical method is a multiple analysis with Ordinary Least Square (OLS) technique. The results show that the industrialization has no a significant effect on migration, while the population growth has a significant effect on internal migration.https://doi.org/10.26905/jmdk.v7i1.2706